If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x(9x + -4) = 0 Reorder the terms: 9x(-4 + 9x) = 0 (-4 * 9x + 9x * 9x) = 0 (-36x + 81x2) = 0 Solving -36x + 81x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '9x'. 9x(-4 + 9x) = 0 Ignore the factor 9.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-4 + 9x)' equal to zero and attempt to solve: Simplifying -4 + 9x = 0 Solving -4 + 9x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 9x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 9x = 0 + 4 9x = 0 + 4 Combine like terms: 0 + 4 = 4 9x = 4 Divide each side by '9'. x = 0.4444444444 Simplifying x = 0.4444444444Solution
x = {0, 0.4444444444}
| 3D-2c=-17 | | 2x-8(x+1)=28 | | 4(w+7)= | | C=1-D | | -0.01x^2-0.3x+40=0 | | 14x+62=7x+34 | | 5x^3+10x^2-10=5x | | 3x-5-7x+3= | | -10b=-10 | | f(x)=2(x^2+5) | | (x*4)+(y*5)=28 | | 1x-3y=9 | | F(x)=2x^2+10 | | 1/2(4x-5)=(1/2*4x)-(1/2*5) | | 2162x=36 | | 369297=0.6213x^2+468.84x+14091 | | 143695=0.6213x^2+468.84x+14091 | | (4)3x=(8)x+2 | | 8+log*5(-4x)=9 | | 449174=0.6213x^2+468.84x+14091 | | 4-3r=32-r | | 313885=0.6213x^2+468.84x+14091 | | (4y+4)-(3+3y)=2 | | 185322=0.6213x^2+468.84x+14091 | | 9x=27-2x+2 | | 4x^4-13x^3-8x^2+13x-12=0 | | 2x-2=37 | | 369297=0.6213x^2+468084x+14091 | | 3x*4=x+2*8 | | 8v^2+6v-28=-10 | | 125-v=25-v-1 | | 12+5x=y |